A Case Study in Project Implementation Vijaipur Fertilizer Project - Planning Commission (Planning Commission, 1989)
The Vijaipur Fertilizer Project of National Fertilizers Limited (NFL) approved by Government of India in March, 1984 commenced production in Dec.1987 with difference of only about three months from the scheduled date inspite of nearly six months delay in the receipt of the gas supply. Moreover, the project crossed 100% capacity utilisation level on consistent basis in October 1988 against June 1989 as planned for 90% level. the actual overall cost of the project is about Rs 508 5 crore as against the approved cost of Rs.587.1 crore.
Planning Commission Government of India
Planning Commission Government of India